A Comparison of Neural Decoding Methods and Population Coding Across Thalamo-Cortical Head Direction Cells - Xu, Zishen; Wu, Wei; Winter, Shawn S.; Mehlman, Max L.; Butler, William N.; Simmons, Christine M.; Harvey, Ryan E.; Berkowitz, Laura E.; Chen, Yang; Taube, Jeffrey S.; Wilber, Aaron A.; Clark, Benjamin J. (Frontiers in Neural Circuits, 2019)
Head direction (HD) cells, which fire action potentials whenever an animal points its head in a particular direction, are thought to subserve the animal’s sense of spatial orientation. HD cells are found prominently in several thalamo-cortical regions including anterior thalamic nuclei, postsubiculum, medial entorhinal cortex, parasubiculum, and the parietal cortex. While a number of methods in neural decoding have been developed to assess the dynamics of spatial signals within thalamo-cortical regions, studies conducting a quantitative comparison of machine learning and statistical model-based decoding methods on HD cell activity are currently lacking. Here, we compare statistical model-based and machine learning approaches by assessing decoding accuracy and evaluate variables that contribute to population coding across thalamo-cortical HD cells.